Recovery of Polyphenolic Compounds from Brassica Oleracea Leaves Biowaste by Ultrasound-Assisted and Maceration Extraction: Study of Variables Effect and Kinetics Using Peleg Model - Sepulveda-Cuevas, L; Cerro-Munoz, D (Taylor and Francis Ltd., 2025)
This study compared ultrasound-assisted extraction (UAE) and conventional extraction by maceration (CE) to obtain polyphenolic compounds with antioxidant activity from Brassica oleracea leaves biowaste. Preliminary tests showed that agitation intensity positively affected both the initial recovery rate and the equilibrium concentration of polyphenols with antioxidant activity. The equilibrium extraction time for CE was 150 minutes, while UAE achieved equilibrium in just 90 minutes. UAE also increased the initial recovery rate by more than seven times and improved the total recovery by 12%. Box-Behnken design was used to optimize CE, while factorial design was used for UAE, considering solid/liquid ratio (10–70 g/L), solvent concentration (20–90% v/v) and temperature (20 °C–60 °C). For CE, the highest results were obtained at 60 °C, 70% ethanol/water v/v and 10 g/L ratio, obtaining 1454.7 mg GAE/100 g DW, with 677.4 mg Fe+2/100 g DW of antioxidant capacity and 20.7 mg CA/100 g DW of chlorogenic acid. In comparison, the UAE method under similar conditions and in a lower time, achieved up to 1984.8 mg GAE/100 g DW, 913.4 mg Fe+2/100 g DW, and 39.7 mg CA/100 g DW. In conclusion, UAE is more efficient than CE for extracting polyphenolic compounds with antioxidant activity, allowing higher extraction yields. © 2025 Universidad de Santiago de Chile. Published with license by Taylor & Francis Group, LLC.